Genotoxicity of corrosion eluates obtained from orthodontic brackets in vitro - Angelieri, Fernanda; Marcondes, Joao Paulo C. [UNESP]; Almeida, Danielle Cristina de [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Ribeiroe, Daniel A. (Mosby-elsevier, 2011)
Introduction: The purpose of this study was to evaluate whether corrosion eluates obtained from commercially available orthodontic brackets are able to induce genetic damage in vitro. Material and Methods: Genotoxicity was assessed by the single cell gel (comet) assay using Chinese hamster ovary (CHO) cells. The following orthodontic metallic brackets were used: Morelli (Sorocaba, Brazil); Abzil (Sao Jose do Rio Preto, Brazil); Dentaurum (Pforzheim, Germany); and 3M Unitek (Puchheim, Germany). Each dental bracket was submitted to a corrosion process in a solution containing equal amounts of acetic acid and sodium chloride at 0.1 M concentration for 1, 3, 7, 14, 21, 35, and 70 days. CHO cells were exposed to eluates for 30 minutes at 37 degrees C. The negative control was treated with the same solution used for corrosion process for 30 minutes at 37 degrees C. Independent positive control was performed with methyl methanesulfonate (MMS) (Sigma Aldrich, St. Louis, Mo) at 1 ug/mL for 1 hour. Results: None of the eluates was found to exhibit genotoxicity, regardless of the different commercial brands of orthodontic appliance used. Conclusions: In summary, our results indicate corrosion eluates obtained from orthodontic brackets do not induce genetic damage as assessed by single cell gel (comet) assay. (Am J Orthod Dentofacial Orthop 2011; 139: 504-9)